Architects Registered in Chile by the Census 1865-1895: The Expansion of the Profession - Inostroza Hernández , Carlos (2025)
Architects who practicing in Chile during the second half of the 19th century have been poorly documented due to the scarcity of studies on the subject, which generally focus on emblematic works and relevant positions. According to the national census reports of 1865, 1875, 1885, and 1895, "architect" was among the registered professions, but this statistical background has not been addressed in our disciplinary historiography. Through a quantitative analysis of these results, we have obtained an insight into the universe of architects, their expansion, hierarchical centers in the territory, and groups of foreigners by nationality, which allows us to contribute to the knowledge of the practice of the profesión during this period.